2017
DOI: 10.21660/2017.36.84153
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Factors Affecting Geopolymerization of Low Calcium Fly Ash

Abstract: This paper presents some factors affecting geopolymerization of low calcium fly ash for geopolymeric matrices. Low calcium fly ash samples were collected from two different coal-powered facilities: an Indonesian fertilizer plant and a Japanese power plant. Several series of tests were conducted using various ratios of fly ash to activator as well as ratios of activators to sodium hydroxide molarity. Each matrix consisted of a set molar ratio of three variations of Si/Al (1.5, 2, 2.5), Na2O/SiO2 (0.3-0.38), H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…AAM mortars are mixtures made from precursor materials (fly ash/GGBFS/micro-silica), mixed with a fixed alkaline solution (Na2SiO3+NaOH), and standardized sand. All of these materials are then compacted, demolded, cured as previous papers [10][11][12][13]. Fixed alkali solution ratio of Na2SiO3 to 8 M NaOH of 1.5 is used.…”
Section: Materials and Mixture Compositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…AAM mortars are mixtures made from precursor materials (fly ash/GGBFS/micro-silica), mixed with a fixed alkaline solution (Na2SiO3+NaOH), and standardized sand. All of these materials are then compacted, demolded, cured as previous papers [10][11][12][13]. Fixed alkali solution ratio of Na2SiO3 to 8 M NaOH of 1.5 is used.…”
Section: Materials and Mixture Compositionsmentioning
confidence: 99%
“…In previous work [10][11], the researcher investigated the utilization of low calcium fly ash for alkali-activated (geopolymer) matrices. Researchers developed low calcium fly ash, ground granulated blast furnace slag (GGBFS), and microsilica as binding materials for alkali-activated mortar [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Fly ash-based geopolymer concrete had been developed since several decades ago [1][2][3][4][5][6][7]. Study of geopolymer reinforced concrete beam was also investigated by several researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Alkali-activated fly ash represent promising sustainable alternatives to ordinary Portland cement, with benefits including 70% lower CO2 emission than Portland cement [3], higher mechanical properties [4][5][6], fire resistance [7], thermal resistance [8], lower heat of hydration [9] and heat release [10], strength against chemical attack [11] [12] [11][12], durability in an aggressive environment [13][14], freeze-thaw resistance [15], lower shrinkage in fly ash-based geopolymer [6;16-18], and comparable shrinkage value in blended slag-fly ash geopolymers [19][20]. Conversely, drawbacks include setting periods [21][22], high shrinkage in alkali-activated materials [23][24][25], high salt efflorescence [5], higher carbonation [26], and cracking while curing [27][28]. A compilation of material regarding largescale application of alkaliactivated cement for materials, cements, concrete, structures, tests procedures, and system benefits is presented in [29].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study [22] reported initial and final setting time of type II fly ash paste at 45 and 108 hours. However, initial setting time of OPC (Ordinary Portland Cement) with Vicat Needle by [58] at 30 min and final setting time should not be more than 10 hours.…”
Section: Introductionmentioning
confidence: 99%